2020
DOI: 10.1186/s12906-020-02917-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of Piper chaba Hunt. and its pure compound, piperine, on TRPV1 activation and adjuvant effect

Abstract: Background: Piper chaba Hunt. is used as an ingredient in Thai traditional preparation for arthritis. Its isolated compound is piperine which shows anti-inflammatory activity. Piperine produces a burning sensation because it activates TRPV1 receptor. The TRPV1 activation involved with the analgesic and adjuvant effect. P. chaba Hunt. has not been reported about TRPV1 activation and adjuvant effect. The aim of this study was to investigate the effect of P. chaba extract and piperine on TRPV1 receptor, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We can say that the Nafion polymer membrane is similar to synthetic biological polymer membranes; see the recent review [20]. In this regard, the alkaloid piperine (C 17 H 19 NO 3 ), which stimulates the conductivity of calcium [21] and potassium [22] ions in human cell channels, is of particular interest to study. Indeed, because the Nafion membrane contains negatively charged channels that are the conductors of protons, it is very important to study the interaction of piperine with Nafion.…”
Section: Introductionmentioning
confidence: 99%
“…We can say that the Nafion polymer membrane is similar to synthetic biological polymer membranes; see the recent review [20]. In this regard, the alkaloid piperine (C 17 H 19 NO 3 ), which stimulates the conductivity of calcium [21] and potassium [22] ions in human cell channels, is of particular interest to study. Indeed, because the Nafion membrane contains negatively charged channels that are the conductors of protons, it is very important to study the interaction of piperine with Nafion.…”
Section: Introductionmentioning
confidence: 99%
“…Piperine, as a major active compound in BJK, showed moderate activity on NO-production inhibition with an IC 50 value of 38.89 ± 0.79 mg/mL ( 10 ). Moreover, piperine also has been suggested to activate transient receptor potential vanilloid 1 which is related to being analgesic and counterirritant effects ( 22 ). However, when BJK was loaded into the formula at the concentration of 0.5% w/w, only piperine was detected with the maximum absorbance at 340 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported different biological activities for retrofractamide B. For instance, some authors proposed that besides piperine, retrofractamide B can be responsible for the transient receptor potential vanilloid 1 (TRPV1) activation [47,48]. TRPV1 has become an attractive target for many pathologies, as its activation has roles in the pathogenesis of chronic inflammatory skin diseases, thermogenesis [48], diabetes, and bladder and lung function [49].…”
Section: Semipreparative Hplc Analysismentioning
confidence: 99%